Impact of Artificial Intelligence on Teachers’ Job Satisfaction: Cognition, Ability, and Ethics in the Digital age. - Cavero López, Pablo (2025)
The integration of artificial intelligence in education generates both enthusiasm and concern, particularly regarding ethics, biases, and academic integrity. This study examines how factors such as cognition, ability, vision, ethics, perceived threats, and innovation influence teachers’ job satisfaction when incorporating AI into their classrooms. To this end, a questionnaire was administered to 51 teachers from several educational levels, analyzing their perceptions and competences regarding these technologies.  The results reveal a predominantly positive assessment of AI, especially for its ability to improve teaching practice and to increase job satisfaction. Nevertheless, weaknesses were identified regarding the technical handling of AI, particularly in the ability dimension, highlighting the need for a stronger training. Furthermore, it was observed that cognition impacts teachers’ ethics and vision, and that the perception of innovation is positively associated with job satisfaction.  Likewise threats such as technological dependence or loss of critical thinking are acknowledged, although they do not significantly diminish teachers’ positive evaluation of AI. This study provides empirical evidence on the relationships between cognitive and emotional factors in teachers’ adoption of AI.